Near-Infrared Imaging Using Indocyanine Green for Laparoscopic Lateral Pelvic Lymph Node Dissection for Clinical Stage II/III Middle-Lower Rectal Cancer: A Propensity Score-Matched Cohort Study. Issue 7 (23rd November 2022) - Ohya, Hiroki; Watanabe, Jun; Suwa, Hirokazu; Suwa, Yusuke; Ozawa, Mayumi; Ishibe, Atsushi; Kunisaki, Chikara; Endo, Itaru
Abstract : BACKGROUND: The examination of the efficacy of near-infrared imaging using indocyanine green in laparoscopic lateral pelvic lymph node dissection remains insufficient. OBJECTIVE: The aim of this study was to examine whether near-infrared imaging contributed to an increase in the total number of harvested lateral pelvic lymph nodes in laparoscopic lateral pelvic lymph node dissection. DESIGN: This was a retrospective, multi-institutional study with propensity score matching. SETTINGS: We conducted this study within the framework of the Yokohama Clinical Oncology Group in Japan. PATIENTS: The study population included consecutive patients with middle-low rectal cancer (clinical stage II to III) who underwent laparoscopic lateral pelvic lymph node dissection between January 2013 and February 2018. MAIN OUTCOME MEASURES: The total number of harvested lateral pelvic lymph nodes was compared in laparoscopic lateral pelvic lymph node dissection with and without near-infrared imaging. RESULTS: A total of 172 eligible patients were included; 84 of these patients underwent laparoscopic surgery with near-infrared imaging. After propensity score matching, 58 patients were matched in each of the near-infrared and the non–near-infrared groups. The operation time in the near-infrared group was significantly longer than that in the non–near-infrared group (426 vs 369 min), and the amount of intraoperative blood loss in the near-infrared group was significantly smaller than that in the non–near-infrared group (13 vs 110 mL). The total number of harvested lateral pelvic lymph nodes in the near-infrared group was significantly higher than that in the non–near-infrared group (14 vs 9). There were no significant differences in the postoperative complication rates of the 2 groups. LIMITATIONS: The limitations of the present study include its retrospective design. CONCLUSIONS: This study revealed that laparoscopic lateral pelvic lymph node dissection combined with near-infrared imaging could increase the total number of harvested lateral pelvic lymph nodes without impairing functional preservation. See Video Abstract at http://links.lww.com/DCR/B800 . This study was registered with the Japanese Clinical Trials Registry as UMIN000041372 (http://www.umin.ac.jp/ctr/index.htm ). IMÁGENES CASI-INFRARROJAS UTILIZANDO VERDE DE INDOCIANINA EN LA DISECCIÓN LAPAROSCÓPICA DE GANGLIOS LINFÁTICOS PÉLVICOS LATERALES EN CASOS DE CÁNCER DE RECTO MEDIO-INFERIOR DE ESTADIO CLÍNICO II / III: ESTUDIO DE COHORTES CON PUNTUACIÓN DE PROPENSIÓN ANTECEDENTES: El examen de la eficacia de las imágenes casi-infrarrojas utilizando le verde de indocianina en la disección laparoscópica de los ganglios linfáticos pélvicos laterales sigue siendo insuficiente. OBJETIVO: El objetivo de este estudio fue examinar si las imágenes casi-infrarrojas contribuyeron a un aumento en el número total de ganglios linfáticos pélvicos laterales recolectados durante su disección laparoscópica. DISEÑO: Estudio retrospectivo, multi-institucional con emparejamiento por puntuación de propensión. AJUSTES: Estudio realizado dentro el marco establecido por el Grupo de Oncología Clínica de Yokohama, Japón. PACIENTES: La población estudiada incluyó pacientes consecutivos con cáncer de recto medio-bajo (estadio clínico II a III) que se sometieron a una disección laparoscópica de los ganglios linfáticos pélvicos laterales entre enero de 2013 y febrero de 2018. PRINCIPALES RESULTADOS MEDIDAS: El número total de ganglios linfáticos pélvicos laterales extraídos se comparó en la disección laparoscópica de ganglios linfáticos pélvicos laterales con y sin imágenes casi-infrarrojas. RESULTADOS: Se incluyeron un total de 172 pacientes elegibles; 84 de estos pacientes se sometieron a cirugía laparoscópica con imágenes casi-infrarrojas. Después del emparejamiento por puntuación de propensión, 58 pacientes fueron emparejados en cada uno de los grupos de luz casi-infrarroja y los sin luz. El tiempo de operación en el grupo de luz casi-infrarroja fue significativamente más largo que en el grupo sin luz (426 frente a 369 min), y la cantidad de pérdida de sangre intraoperatoria en el grupo de luz casi-infrarroja fue significativamente menor que en el grupo sin luz (13 frente a 110 ml). El número total de ganglios linfáticos pélvicos laterales recolectados en el grupo de luz casi-infrarroja fue significativamente mayor que en el grupo sin luz (14 frente a 9). No hubo diferencias significativas en las tasas de complicaciones posoperatorias de los dos grupos. LIMITACIONES: Las limitaciones del presente estudio incluyen su diseño retrospectivo. CONCLUSIONES: Este estudio reveló que la disección laparoscópica de los ganglios linfáticos pélvicos laterales combinada con imágenes casi-infrarrojas podría aumentar el número total de ganglios linfáticos pélvicos laterales recolectados sin afectar la preservación funcional. Consulte Video Resumen en http://links.lww.com/DCR/B800 . (Traducción—Dr. Xavier Delgadillo ) Este estudio se registró en el Registro de Ensayos Clínicos de Japón como UMIN000041372 (http://www.umin.ac.jp/ctr/index.htm ).